Datação de Processos Diagenéticos em Arenitos-Reservatório de Hidrocarbonetos: Uma Revisão Conceitual - MARASCHIN, ANDERSON JOSÉ; MIZUSAKI, ANA MARIA (Pesquisas em Geociências, 2008)
Geochronology has became a powerfull tool for diagenetic studies in siliciclastic rocks as it supply parameters for the definition of their depositional or diagenetic ages. This development occurred particularly in the last decades, with analytical techniques improvements and application of oil exploration. Sandstones are important hydrocarbon reservoir-rocks in many basins of the world. Sandstones devoid of fossils with defined ages lack precise chronostratigraphic definition. Such lack of definition limits the precision of the generation-migration-accumulation models developed for the exploration and exploitation of these reservoirs. However, many sandstones contain diagenetic minerals which represent the possibility of dating the deposition of these sandstones, or episodic diagenetic fluid migration through radiometric 40K-40Ar, 40Ar-39Ar and 87Rb-87Sr methods. In the present work, we show that these methods have been successfully applied to samples of reservoirsandstones all over the world. The improvement of the radiometric methods applied to sedimentary rocks yielded significant results concerning depositional or diagenetic ages.